2005
DOI: 10.1111/j.1365-3040.2004.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of QTL underlying whole‐plant physiology in Arabidopsis thaliana: δ13C, stomatal conductance and transpiration efficiency

Abstract: Water limitation is one of the most important factors limiting crop productivity world-wide and has likely been an important selective regime influencing the evolution of plant physiology. Understanding the genetic and physiological basis of drought adaptation is therefore important for improving crops as well as for understanding the evolution of wild species. Here, results are presented from quantitative trait loci (QTL) mapping of flowering time (a drought escape mechanism) and carbon stable isotope ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
175
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 65 publications
6
175
1
Order By: Relevance
“…However, under this mechanism, greater discrimination would be indicative of greater WUE, which is exactly the opposite of how d 13 C is interpreted when stomatal conductance is assumed to be the dominant mechanism affecting both d 13 C and WUE. Our finding stresses the importance of identifying the mechanism underlying variation in d 13 C in quantitative genetic studies (Juenger et al 2005), when interpreting the ecological significance of this variation. Figure 4 Carbon isotope data suggest that amphistomy (greater stomatal ratio) decreases the distance between stomata and chloroplast.…”
Section: Structure-function Relationship Reveals the Mechanistic Signmentioning
confidence: 92%
See 1 more Smart Citation
“…However, under this mechanism, greater discrimination would be indicative of greater WUE, which is exactly the opposite of how d 13 C is interpreted when stomatal conductance is assumed to be the dominant mechanism affecting both d 13 C and WUE. Our finding stresses the importance of identifying the mechanism underlying variation in d 13 C in quantitative genetic studies (Juenger et al 2005), when interpreting the ecological significance of this variation. Figure 4 Carbon isotope data suggest that amphistomy (greater stomatal ratio) decreases the distance between stomata and chloroplast.…”
Section: Structure-function Relationship Reveals the Mechanistic Signmentioning
confidence: 92%
“…Our third goal was to more directly dissect the mechanistic significance of variation in these stomatal traits by evaluating their association with variation in carbon isotope discrimination (d 13 C), a widely used indicator of integrated water-use efficiency (WUE) in quantitative genetic studies (McKay et al 2003(McKay et al , 2008Juenger et al 2005). Both traits potentially affect water-use efficiency and carbon isotope discrimination; however, because each trait influences different steps in the CO 2 diffusion pathway (atmosphere / inside of leaf vs. inside of leaf / chloroplasts; see Materials and Methods and Discussion), the correlation between these different stomatal traits and d 13 C can be used to infer which portion of this diffusion pathway is more functionally significant in these species.…”
mentioning
confidence: 99%
“…Although one study in Arabidopsis found a major QTL encoding the transcription factor, ERECTA, which explained up to 64% of the phenotypic variation in a Landsberg × Columbia RI population (Masle et al 2005), studies evaluating genetic variation for carbon isotope discrimination in other plant species have identified multiple QTLs of smaller effect associated with the trait. For example, in another population of Arabidopsis, two to five QTLs were identified Juenger et al 2005). In rice, one to three QTLs for Δ 13 C were identified by Laza et al (2006) and Takai et al (2006), three to five by Price et al (2002), and four by Xu et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Such a selection has been facilitated by the widespread use of δ 13 C, a proxy for daytime TE based on the carbon isotope discrimination that occurs during photosynthesis (8). This strategy has been successfully implemented in both model plants and crops to detect genomic regions associated with the control of TE, which are being exploited in breeding programs (9,10), or serve as starting points to investigate the genetic determinism and ecological significance of the variation in TE (11)(12)(13).…”
mentioning
confidence: 99%